TRIPS Agreement and developing countries (UN New YorkUS, 1996)
Seeks to assess the policy implications of the Agreement on Trade-Related Aspects of Intellectual Property Rights (the TRIPS Agreement) for developing countries and to delineate on agenda for the transitional period of implementation.
DC